Early expansion of activated adaptive but also exhausted NK cells during acute severe SARS-CoV-2 infection - Claus, Maren; Pieris, Naomi; Urlaub, Doris; Bröde, Peter; Schaaf, Bernhard; Durak, Deniz; Renken, Frank; Watzl, Carsten (Frontiers in Cellular and Infection Microbiology, 2023)
The analysis of immunological parameters during the course of a SARS-CoV-2 infection is of great importance, both to identify diagnostic markers for the risk of a severe course of COVID-19, and to better understand the role of the immune system during the infection. By using multicolor flow cytometry we compared the phenotype of Natural Killer (NK) cells from hospitalized COVID-19 patients during early SARS-CoV-2 infection with samples from recovered and SARS-CoV-2 naïve subjects. Unsupervised high-dimensional analysis of 28color flow cytometric data revealed a strong enrichment of NKG2C expressing NK cells in response to the acute viral infection. In addition, we found an overrepresentation of highly activated NK cell subsets with an exhausted phenotype. Moreover, our data show long-lasting phenotypic changes within the NK cell compartment that did not completely reverse up to 2 months after recovery.